إعتبار المقاصد في فقه الأقليات المسلمة في المسائل الإجتهادية : دراسة تأصيلية تطبيقية - مباركي نور الدين (Universty Of El-oued جامعة الوادي, 2025)
الملخص: لقد احتاج هذا البحث الموسوم بـ: اعتبار المقاصد في فقه الأقليات المسلمة في المسائل الاجتهادية دراسة تأصيلية" إلى إشكالية رئيسية تبحث في مدى اعتبار وحضور مقاصد الشريعة في القضايا الاجتهادية المتعلقة بفقه الأقليات المسلمة وكيف استطاعت المقاصد أن تكون هي البوصلة لهذا الفقه أدلة وتعليلاً وترجيحاً؟ وقد جاء البحث في فصلين؛ الفصل الأول: خصص لمعرفة ماهية المقاصد وفقه الأقليات المسلمة، وانتظم في مبحثين؛ الأول لبيان ماهية المقاصد، وأهميتها، وأقسامها، والثاني لتعريف فقه الأقليات، وخصائصه، وأهميته، أما الفصل الثاني: فقد تناول أثر المقاصد في فقه الأقليات، وانطوى على ثلاثة مباحث الأول: للعبادات، والثاني: لفقه الأسرة والأحوال الشخصية، والثالث: للمعاملات، حيث تضمن كل مبحث أربعة مسائل اجتهادية ودراستها من الجانب الفقهي، ثم المنحى المقاصدي لكل مسألة أدلة وتعليلاً وترجيحاً، في إطار النظر المقاصدي، مع استخراج المقاصد المعتبرة العامة والخاصة والجزئية وغيرها من كل مسألة مبحوثة. ثم ختم البحث بمجموعة من النتائج التي هي عصارة هذه الدراسة وثمرتها، وركزت خاصة على ثبوت المقاصد في قلب نوازل الأقليات المسلمة وتوجيهها نحو تحقيق مقاصد الأحكام، كما أوصت الدراسة بتكثيف البحوث العلمية حول قضايا الأقليات المسلمة، وفق منهجية مقاصدية متكاملة، وتأهيل أهل الفتوى للتمرس بالصناعة المقاصدية في معالجة نوازل الأقليات المسلمة Résumé : فرنسية أو انجلزية This research entitled by: “Considering the Purposes in the Jurisprudence of Muslim Minorities , a fundamental study” required a main problematic that is to which extent the Purposes of Sharia are considered and present in the jurisprudential issues related to the jurisprudence of Muslim minorities, and how were the purposes being able to be the compass for this jurisprudence as evidencing, explaining, and weighting? The research is divided into two chapters: The first chapter was devoted to know the nature of the purposes and the jurisprudence of Muslim minorities, it was organized into two sections: the first: to explain the nature of the purposes, their importance and their divisions, and the second: to define the jurisprudence of minorities, its characteristics, and its importance. Whereas the second chapter dealt with the impact of the purposes in the jurisprudence of minorities, It included three sections: the first is for the worship, the second is for the family jurisprudence, and the third is for transactions, each section included four diligence issues from the perspective of jurisprudential disagreement, then the purpose approach for each issue, evidencing, explaining, and weighting within the framework of purposes view, within the extraction of the general, specific, partial, and other considered purposes from each researched issue. The research is concluded with a set of results that are the essence and the fruit of this study, it focused in particular on binding the purposes at the heart of the new calamities of Muslim minorities and directing them towards achieving the purposes of the rulings. The study also recommended intensifying the research on the issues of Muslim minorities according to an integrated purposes “Maqasid” methodology, and qualifying fatwa scholars to practice the purposes “Maqasid” industry in the treatment of the problems of Muslim minorities.
أطروحة دكتوراه تخصص الفقه وأصوله في العلوم الإسلامية
Keywords: المقاصد ، فقه الأقليات المسلمة ، المسائل الاجتهادية; Maqasid; Jurisprudence of Muslim Minorities; Ijtihadic Issues